Abnormal temperature effect on tensile strength of Mg-13Gd-2Y-0.5Zr alloy. (July 2020) - Chen, Xiaoya; Li, Quanan; Zhu, Limin; Chen, Jun
Abstract: In this work, the microstructures and tensile properties of Mg-13Gd-2Y-0.5Zr (wt.%) alloy at different temperatures were studied. The results show that the tensile strength of Mg-13Gd-2Y-0.5Zr alloy increases first and then decreases with the increase of tensile temperature (showing abnormal temperature effect of tensile strength). The ultimate tensile strength is 315 MPa at 250 °C, which is 22.01% higher than that of 258 MPa at room temperature. The petal-like β′ phase diffusely distributes in the α-Mg matrix, and has a good coherent interface with the α-Mg matrix. The dislocation strengthening caused by Gd and Y elements and coherent strengthening of petal-like β′ are the main reasons for abnormal temperature effect of tensile strength. Highlights: The Mg-13Gd-2Y-0.5Zr alloy exhibits an abnormal temperature effect of tensile strength. The petal-like β′ diffusely distributes in the α-Mg matrix and is in a coherent relationship with α-Mg. The coherent strengthening of β′ phase is the main strengthening me'chanism.